JURIDICAL ANALYSIS OF THE CONSTITUTIONAL COURT LAWSUIT ON THE MINIMUM EDUCATION REQUIREMENTS FOR PRESIDENTIAL AND VICE-PRESIDENTIAL CANDIDATES - De'frantika, Reyhan Pradipa; Saputra, M. Rizky Ramadan; Aizad, M. (LPPM Univ. Ibn Khaldun Bogor, 2026)
The lawsuit regarding the minimum educational requirements for presidential and vice-presidential candidates before the Constitutional Court (MK) has become a crucial issue in constitutionalism and democracy in Indonesia. This issue arose when some parties considered that the provisions regarding minimum educational levels in the general election law had the potential to limit citizens' political rights, contradict the principle of equality before the law, and violate the constitutional right to be elected. This study aims to conduct a legal analysis of the Constitutional Court's ruling on this lawsuit, using a normative and legislative approach, including a review of Law Number 7 of 2017 concerning General Elections, the 1945 Constitution, and previous Constitutional Court decisions. The analysis shows that the Constitutional Court considers the principles of political accessibility, justice, and harmonization between state interests and individual rights in determining the reasonableness of educational requirements. The Constitutional Court tends to emphasize that excessive requirements can hinder political participation and are potentially discriminatory, necessitating a balanced constitutional interpretation. The findings of this study are expected to contribute to the understanding of constitutional law, the formulation of general election policies, and the strengthening of democracy in Indonesia. Thus, this study emphasizes the importance of aligning the formal requirements for candidates for head of state with the principles of citizens' constitutional rights.